2003
DOI: 10.1614/0890-037x(2003)017[0127:sczmcs]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Corn (Zea mays) Cultivar Sensitivity to AE F1303601

Abstract: Eight sweet corn cultivars were evaluated for tolerance to AE F130360 in five field experiments conducted over 2 yr in Ontario. AE F130360 was applied postemergence at 70 and 140 g ai/ha, the latter rate representing a spray overlap in the field. Response to AE F130360 varied with respect to sweet corn cultivar and herbicide rate. Minimal crop injury was observed in seven of the eight cultivars. One cultivar, ‘DelMonte 2038’, was extremely sensitive, showing 94% or more injury for all site-years. Plant height … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 14 publications
6
22
0
Order By: Relevance
“…Stall and Bewick (1992) determined that four of 12 hybrids demonstrated a response to nicosulfuron rate and marketable yield was significantly lower at higher rates. Similar sweet corn yield responses were also reported with other herbicides such as AE F130360 (foramsulfuron), CGA 152,005 (prosulfuron), primisulfuron, and rimsulfuron (Diebold et al, 2003;O'Sullivan et al, 1998;Sikkema 2001, 2002;Van Wychen et al, 1997).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Stall and Bewick (1992) determined that four of 12 hybrids demonstrated a response to nicosulfuron rate and marketable yield was significantly lower at higher rates. Similar sweet corn yield responses were also reported with other herbicides such as AE F130360 (foramsulfuron), CGA 152,005 (prosulfuron), primisulfuron, and rimsulfuron (Diebold et al, 2003;O'Sullivan et al, 1998;Sikkema 2001, 2002;Van Wychen et al, 1997).…”
Section: Resultssupporting
confidence: 71%
“…Sensitivity of sweet corn to herbicides is dependent on the application rate, hybrid, and environmental conditions. Some of the commonly grown sweet corn hybrids in Ontario such as Calico Belle, Delmonte 2038, and GH2684 have shown sensitivity to other herbicides such as AE F130360 (foramsulfuron), bentazon, CGA152005 (prosulfuron), mesotrione, nicosulfuron, primisulfuron, and RPA201772 (isoxaflutole) (Diebold et al, 2003(Diebold et al, , 2004Sikkema 2001, 2002;O'Sullivan et al, 1999O'Sullivan et al, , 2000Robinson et al, 1993). Hybrid sensitivity is an important factor for registration of herbicides in sweet corn.…”
mentioning
confidence: 99%
“…At 3 WAT, all treatments were not statistically different (Table 4). These findings are similar to those records after treatment with nicosulfuron [2], nicosulfuron plus rimsulfuron [5], foramsulfuron [25] and thifensulfuron-methyl [26]. Both plant height and maize injury showed similar trends.…”
Section: Field Experimentssupporting
confidence: 86%
“…Diebold et al (2003Diebold et al ( , 2004 [10] reported up to 94% reduction in yield with formsulfuron in sweet maize. Similar yield reduction were reported with mesotrione [13], nicosulfuron [14], foramsulfuron [10] and nicosulfuron plus rimsulfuron [24,25] in some sensitive sweet maize hybrids. The potential for and level of crop injury from use of nicosulfuron, mesotrione, and foramsulfuron on any specific sweet maize hybrid is conditioned largely by CYP alleles at the nsf1/ben1 locus on the short arm of chromosome 5 [27].…”
Section: Yieldmentioning
confidence: 99%
“…Sensitivity of sweet maize to herbicides is dependent on the application dose, hybrid, and environmental conditions. Sweet maize hybrid sensitivity has been documented for foramsulfuron [10], bentazon [11], prosulfuron [12], mesotrione [13], nicosulfuron [14,15], primisulfuron [16], isoxaflutole [17], and thifensulfuron-methyl [18].…”
Section: Introductionmentioning
confidence: 99%